Enhancing the extremely high thermal conduction of graphene nanoribbons - Li, Xiuqiang; Zhang, Gang (Frontiers in Physics, 2013)
Graphene and Graphene nanoribbons (GNRs) are found to have superior high thermal conductivity favorable for high-performance heat dissipation. In this letter, by using molecular dynamics simulations, we show that constructing specific structure can further enhance high thermal conduction of GNRs. By introducing a small gap at the center, the average heat flux (thermal conductivity) can be enhanced by up to 23%, the corresponding increase in total heat current is 16%. This unusual thermal conduction enhancement is achieved by an intriguing physical mechanism of suppress phonon-phonon scattering. Our findings uncover new mechanism to increase thermal conduction of GNRs.